The Relationship Between Alexithymia And Compulsive Shopping In Young Adults - Barbera, Martina; Rizzo, Amelia (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
Although previous studies have investigated factors contributing to compulsive shopping, the specific role of alexithymia and its influence on emotion regulation in predicting this behavior remains underexplored. The study explored the link between alexithymia and compulsive shopping in young adults, focusing on whether emotion regulation difficulties predict problematic shopping behavior. A sample of 220 Italian young adults was assessed using the Toronto Alexithymia Scale (TAS-20) and the Shopping Behaviour Scale (SBS). Multiple regression analysis revealed that alexithymia's three dimensions explained 4.8% of the variance in compulsive shopping (F=3.657; p=0.013). Externally oriented thinking was the only significant predictor, while difficulty identifying and describing feelings were not. The findings suggest that individuals more focused on external realities are at higher risk for compulsive shopping. Improving emotional awareness and regulation may help reduce this behavior in young adults.